National review of reported Yellow fever vaccine incidents in the UK. Issue 47 (May 2022) - Gnanadurai, Roshina; Campos-Matos, Ines; Kanagarajah, Sanch; Geary, Katie; Simons, Hilary; Patel, Dipti
Abstract: Background: Yellow fever (YF) vaccination is the single most important preventative measure against YF infection, however the live attenuated vaccine has associated serious adverse events. All YF vaccinations in England, Wales and Northern Ireland (EWNI) are administered in YF Vaccination Centres and comply with National Travel Health Network and Centre (NaTHNaC) Conditions of Designation and Code of Practice, including reporting of vaccine incidents to NaTHNaC. In this study we evaluated the number and type of YF vaccine incidents in EWNI to identify areas for improvement. Methods: NaTHNaC's telephone advice line database was retrospectively searched from 1st January 2016 to 31st December 2018 for YF vaccine incidents. Calls were categorised and analysed according to incident type. Results: Seventy-eight YF vaccine incidents were reported from a total of 17250 calls. The commonest incident was incorrect timing of measles, mumps and rubella vaccine in relation to YF vaccine, where the recommended 28-day interval was not observed (n = 21). Other incidents included accidental partial vaccination (n = 11), inappropriate vaccination (n = 5) and invalid vaccination due to expiry or cold chain breach (n = 4). Inadvertent vaccination in contraindicated individuals occurred in two travellers with thymectomies (resulting in one death), and five immunocompromised travellers. Conclusions: YF vaccine incidents represent a small proportion of total calls. Similar incidents likely occur with other vaccines, but YF vaccine incidents are of particular concern; whilst most incidents were not harmful, vaccination in contraindicated individuals resulted in one death. These findings helped to inform new guidance and update training for staff in YF vaccination centres.